Reconnection X‐Line Orientations at the Earth's Magnetopause. Issue 12 (24th November 2021) - Fuselier, S. A.; Webster, J. M.; Trattner, K. J.; Petrinec, S. M.; Genestreti, K. J.; Pritchard, K. R.; LLera, K.; Broll, J. M.; Burch, J. L.; Strangeway, R. J.
Abstract: Observations from the magnetospheric multiscale mission in or near electron diffusion regions (EDRs) at the Earth's magnetopause are used to determine the orientation of reconnection X‐lines. The results highlight cross‐scale coupling of magnetic reconnection and the differences between component and anti‐parallel reconnection. These observations are consistent with a model that has a continuous, component reconnection X‐line that extends many Earth Radii (RE ) across the dayside magnetopause when the interplanetary magnetic field (IMF) is southward and |BY | ∼ |BZ |. Encounters anywhere along the X‐line have similar cross‐section structure in the direction normal to the magnetopause, indicating that component reconnection is quasi‐two‐dimensional, at some scale larger than the electron scale. EDR encounters far from this primary component X‐line may be associated with transient or spatially limited reconnection structures. On the magnetopause flanks on either side of the component X‐line, there are regions where anti‐parallel reconnection occurs. These regions dominate the entire dayside magnetopause when the IMF is southward and |BY | << |BZ |. In parts of these regions, observations in or near EDRs are consistent with reconnection occurring at a series of short, anti‐parallel reconnection X‐lines. These X‐lines may be quasi‐stationary or propagating along an anti‐parallel ridge at the magnetopause. In other parts of these regions, X‐lines may be much longer. Plain Language Summary: Magnetic reconnection is the process that couples the solar wind and the Earth's magnetosphere. This process produces long reconnection lines that stretch across the Earth's magnetopause. This paper describes the orientation of these reconnection lines. Key Points: Magnetospheric multiscale observations are used to determine the orientation of reconnection X‐lines at the Earth's magnetopause For southward interplanetary magnetic field and BY ∼ BZ, there is a long, continuous, component reconnection X‐line extending many RE across the dayside magnetopause In high shear regions, there may be many, short, anti‐parallel reconnection X‐lines or a long X‐line along a high magnetic shear ridge